Construcción narrativa del sentido de vida una mujer después del fallecimiento de su esposo - Castellanos Vanegas, Karen Sofía; Díaz Góngora, Martha Catalina (Universidad Antonio Nariño, 2024)
The main objective of this research was to analyze the narratives of a woman in relation to her meaning in life after the death of her husband, through a case study. This research arises from the need to explore the perception of the meaning of life that a widowed woman creates, which can constitute a crucial stage in the life cycle of a person that can influence to a certain extent the continuity of the life project of the person these women.